Evaluasi Pengalaman Pengguna dengan Menggunakan User Experience Questionnaire Perpustakaan Digital - Riche Riche; Sophya Hadini Marpaung (STMIK Budi Darma, 2021)
This study uses the User Experience Questionnaire (UEQ) to assess user experience in the STMIK Mikroskil digital library. In detail, research activities were carried out in several stages, namely by reinventing and determining the formulation of the problem to be solved, conducting literature studies, observing the STMIK Mikroskil library website, designing questionnaires, collecting data, and drawing conclusions. The User Experience Questionnaire (UEQ) is used to assess a system or find out the extent of the user experience in order to get a comprehensive impression of the experience of users or end users of a system. In this study it was found that the usability/user experience of the STMIK Mikroskil digital library for all available services was positive or decent